(The research Of Chitosan For Flocculan In Wastewater Treatment For Tapioca Industries) - Sapto Hartanto, Eddy; Bastaman, Syarif (Warta Industri Hasil Pertanian, 2006)
The research of chitosan for flocculation in wastewater treatment for tapioca industry has been conducted.The researchs goal is to know ability of chitosan for tapioca industrial wastewater treatment.Concentration of coagulant A12 (SO4)3 14 H2O IS 75 MG/1 ON Ph 8 condition.Flocculants chitosan and polymer PN 161 concentrations are 30 mg/1,45 mg/1 and setting 15 minute,30 minute,and 45 minute.The result showed that the formula tawas and chitosan 45 mg/1 on pH 8 and settling time 45 minute was the best treated.The result analysis pollutants each are turbidity from 440 NTU to 29 NTU,TSS from 282 mg/1 to 20,24 mg/1,BOD 861 mg/1 to 88,25 mg/1,COD 1851,3 mg/1 to 151,25 mg/1 and pH 5,67 to pH 6,21.The quality of wastewater treatment with that formulation has met kep men LH No. KEP 51/10/1995 standard regulation for tapioca industrial wastewater.